Precarity and Physical Education - Kirk, David (Revista da ALESDE, 2018)
This paper explores the concept of precarity and its relevance for physical education. I argue that precarity is closely related to neoliberal practices of privatization and free-markets, and that these practices have been exerting an influence on physical education for some time. As the digitization of education gains momentum, I suggest physical educators cannot afford to be complacent about their future place in the school curriculum. Nor can they ignore the rise of precarity and its detrimental influence on the young people they teach. Physical educators have long argued that they make a contribution to young people’s affective development, in terms of their motivation, resilience, cooperation and interest. Arguably, in the face of rising precarity and its ill effects on young people’s mental health and wellbeing, there is a need for physical educators to develop ‘pedagogies of affect’, that take affective learning as its main concern. Teachers themselves may become victims of precarity as education in the Global North, once regarded as a mainly public good, increasingly is privatised. The neoliberal imperative to maximise profit at whatever cost to human wellbeing could result in teachers’ working conditions deteriorating, further adding to what is for many an already high stress occupation. I conclude that we may need to rethink the critical pedagogy project in an age of precarity.